2023
DOI: 10.3389/fvets.2023.1287676
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to identifying spermatozoa proteins in Indonesian native Madura bulls

Zulfi Nur Amrina Rosyada,
Berlin Pandapotan Pardede,
Ekayanti Mulyawati Kaiin
et al.

Abstract: Proteins assist sperm mature, transit the female reproductive tract, and recognise sperm oocytes. Indigenous Indonesian bulls, Madura bulls, have not been studied for reproductive proteomics. As local Indonesian beef livestock, Madura cattle assist in achieving food security; hence, their number must be improved. Thus, the identification of molecular proteomics-based bull fertility biomarkers is needed. This study aimed to characterise the sperm fertility function of the superior Madura bull (Bos indicus × Bos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(61 reference statements)
0
1
0
Order By: Relevance
“… Pardede et al (2022) reported that although the quality of semen met specific requirements and was considered to be of good quality, three out of six bulls in the field showed a low fertility rate (<50%). Recent research has found various gene and protein molecules in spermatozoa that play an essential role in the reproductive process of bulls, mainly the physiological functions of sperm oocytes, which are believed to be able to predict bull fertility accurately ( Özbek et al, 2021 ; Li et al, 2016 ; Pardede et al, 2024 ; Rosyada et al, 2023a ). Furthermore, this is due to the involvement of more complex molecular mechanisms in spermatozoa, including the loss of spermatozoa surface protein required for fertilization ( Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“… Pardede et al (2022) reported that although the quality of semen met specific requirements and was considered to be of good quality, three out of six bulls in the field showed a low fertility rate (<50%). Recent research has found various gene and protein molecules in spermatozoa that play an essential role in the reproductive process of bulls, mainly the physiological functions of sperm oocytes, which are believed to be able to predict bull fertility accurately ( Özbek et al, 2021 ; Li et al, 2016 ; Pardede et al, 2024 ; Rosyada et al, 2023a ). Furthermore, this is due to the involvement of more complex molecular mechanisms in spermatozoa, including the loss of spermatozoa surface protein required for fertilization ( Li et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%